2011
DOI: 10.3390/toxins3101332
|View full text |Cite
|
Sign up to set email alerts
|

Ricinus communis Intoxications in Human and Veterinary Medicine—A Summary of Real Cases

Abstract: Accidental and intended Ricinus communis intoxications in humans and animals have been known for centuries but the causative agent remained elusive until 1888 when Stillmark attributed the toxicity to the lectin ricin. Ricinus communis is grown worldwide on an industrial scale for the production of castor oil. As by-product in castor oil production ricin is mass produced above 1 million tons per year. On the basis of its availability, toxicity, ease of preparation and the current lack of medical countermeasure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
188
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(197 citation statements)
references
References 282 publications
(341 reference statements)
2
188
0
7
Order By: Relevance
“…Despite several reports of accidental poisoning in humans by unprocessed seeds of R. communis (De Paepe et al 2005, Nishiyama et al 2005, Lucas et al 2006, Al-Tamimi et al 2008) cases of poisoning in animals have occurred after the intake of processed seeds (Worbs et al 2011). In Brazil, the data reported to date were mainly from experimental studies in cattle, sheep and rabbits (Armién et al 1996, Brito & Tokarnia 1997, Tokarnia & Döbereiner 1997 and spontaneous cases of poisoning in cattle have not been described.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Despite several reports of accidental poisoning in humans by unprocessed seeds of R. communis (De Paepe et al 2005, Nishiyama et al 2005, Lucas et al 2006, Al-Tamimi et al 2008) cases of poisoning in animals have occurred after the intake of processed seeds (Worbs et al 2011). In Brazil, the data reported to date were mainly from experimental studies in cattle, sheep and rabbits (Armién et al 1996, Brito & Tokarnia 1997, Tokarnia & Döbereiner 1997 and spontaneous cases of poisoning in cattle have not been described.…”
Section: Introductionmentioning
confidence: 80%
“…The cattle were observed ingesting the aerial parts of the plant, seeds were present in the digestive systems of the necropsied cattle, and fallen trees showed signs of consumption. These findings are important for the diagnosis of poisoning because necropsy and histological lesions are nonspecific (Worbs et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ricin protein, a toxic protein with 60 kDa which is contained in R. communis seeds (WORBS et al, 2011), cannot be the active compound against H. contortus eggs, although it is known that the surface of H. contortus eggshells contains galactose carbohydrate (PALMER; McCOMBE, 1996;JURASEK et al, 2010;HILLRICHS et al, 2012), which is a binding site for ricin. Trypsin inhibitor activity, albeit weak, was also observed in the CERN fraction of R. communis.…”
Section: Discussionmentioning
confidence: 99%
“…The acceptable daily castor oil intake (for human) of 0 to 0.7 mg/kg body weight has been established by the food and agriculture organization/world health organization (8). Different human or animal cases of poisoning with castor bean have been reported (10,11). The observational human case series study of Thornton et al (2014) showed that because of the existence of ricin in the castor bean seed, serious outcomes after ingestions of the seeds of the castor bean plant might occur.…”
Section: Discussionmentioning
confidence: 99%